Efektivitas Metode Talaqqi Menghafal Al-Qur’an di MI/SD: Review Jurnal - Khotimah, Maulidy Putri Khusnul; Faliani, Eli; nadlir, Nadlir (Universitas PGRI Semarang, 2024)
This study aims to determine the effectiveness of the Talaqqi method in memorizing the Qur'an among students at the MI/elementary school level. This research employs a literature review method with a qualitative approach. The article was written by applying inclusion and exclusion criteria. Based on a search using the keyword